MODEL PENGEMBANGAN PEMBUATAN GARAM PALUNGAN SEBAGAI PRODUK WISATA DI DESA WISATA LES KECAMATAN TEJAKULA KABUPATEN BULELENG - Kepakisan, Defyartha; Putu Sabda Jayendra; I Wayan Kiki Sanjaya (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2025)
Palungan Salt is a unique tourism potential in Les Tourism Village, Tejakula District, Buleleng Regency. This tourism product not only offers salt processed using traditional methods, but also prioritizes aspects of education, cultural preservation, and community empowerment. It is managed by local entrepreneurs with the aim of collecting, storing, preserving, and introducing Palungan Salt to tourists as an authentic and sustainable attraction. This study highlights the potential and appeal of Palungan Salt, explained through the 4A theory: attractions (unique and educational attractions), accessibility (ease of access to the location), facilities (supporting facilities for tourists), and additional services (additional services to support comfort). The results indicate that Palungan Salt has high selling value as an educational tourism destination as well as a creative economy that can strengthen the image of Les Tourism Village in the tourism arena. Such as limited infrastructure, minimal promotion, low human resource capacity, limited funding, and less than optimal strategic partnerships with educational institutions or the private sector. To overcome these obstacles, the study designed a development model based on community participation, improved facilities, integrated educational programs, sustainable digital promotion, and cross-sector collaboration to strengthen the local economy and preserve cultural heritage. The resulting development model is expected to serve as a strategic reference for managers, village governments, and other stakeholders in improving the quality and number of tourist visits. Furthermore, this model also plays a role in improving operational management, marketing, and the management of local wisdom-based tourist attractions, so that Palungan Salt can become a superior tourism product that provides economic and social benefits to the Les Village community.